PENGARUH PENGGUNAAN ICEBREAKER TERHADAP PRESTASI BELAJAR SISWA PADA POKOK BAHASAN PENCEMARAN LINGKUNGA DI KELAS X SMA NEGERI 1 KAMPAR - Marni Alhuda Alhuda; Yuslim Fauzia Fauzia; Imam Mahadi Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Has do reasearch to find effect use icebreaker for student achievement on the subject of environment pollution in class X SMA N 1 Kampar and to find what category classified increase student achievement on the subject of environment pollution in class X SMA N 1 Kampar. Form of research is a experiment design research with pretest-posttest design. The sample consisted of two classes, X MIA 2 class as experiment class and X MIA3  class as control class that randomly selected after testing normality and homogeneity. Experiment class was treated with implementing Icebreaker and the control class was treated conventional method. Analysis of data used t-test. The results showed that Tcount > Ttable (4,06 > 1,67). It means that using Icebreaker can improve student’s achievement on the subject of environmental pollution in class X of SMAN 1 Kampar. The category improvement of student’s achievement in experiment class was  high  category  ( N-Gain = 0,83) and  in control class was  medium  category (N-Gain =0,7). Keyword : Icebreaker, learning achievement, environmental pollution